Interpreting the cross-sectional flow field in a river bank based on a genetic-algorithm two-dimensional heat-transport method (GA-VS2DH) - Su, Xiaoru; Shu, Longcang; Chen, Xunhong; Lu, Chengpeng; Wen, Zhonghui (Hydrogeology journal, 2016)
Interactions between surface waters and groundwater are of great significance for evaluating water resources and protecting ecosystem health. Heat as a tracer method is widely used in determination of the interactive exchange with high precision, low cost and great convenience. The flow in a river-bank cross-section occurs in vertical and lateral directions. In order to depict the flow path and its spatial distribution in bank areas, a genetic algorithm (GA) two-dimensional (2-D) heat-transport nested-loop method for variably saturated sediments, GA-VS2DH, was developed based on Microsoft Visual Basic 6.0. VS2DH was applied to model a 2-D bank-water flow field and GA was used to calibrate the model automatically by minimizing the difference between observed and simulated temperatures in bank areas. A hypothetical model was developed to assess the reliability of GA-VS2DH in inverse modeling in a river-bank system. Some benchmark tests were conducted to recognize the capability of GA-VS2DH. The results indicated that the simulated seepage velocity and parameters associated with GA-VS2DH were acceptable and reliable. Then GA-VS2DH was applied to two field sites in China with different sedimentary materials, to verify the reliability of the method. GA-VS2DH could be applied in interpreting the cross-sectional 2-D water flow field. The estimates of horizontal hydraulic conductivity at the Dawen River and Qinhuai River sites are 1.317 and 0.015 m/day, which correspond to sand and clay sediment in the two sites, respectively.